THE REACTION OF ANASTOMOSING RIVER FLUVIAL SYSTEMS TO THE OPERATION OF A HYDROELECTRIC POWER PLANT - Bortnyk, S.; Obodovskyi О.; Gerszewski, P.; Szmanda, J.; Луц, М.; Habel М.; Witkowski, K.; Pohorilchuk, N. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The operation of the hydroelectric power plant is one of the main reasons for the transformation of river runoff. The change in the hydrological regime affects several other processes taking place in the river channel, including the transformation of its geomorphological features. The article presents the impact of the Kaniv and Włocławek dams on the hydrological regime of the middle Dnieper River and the lower Vistula River. The nature and magnitude of changes in the Dnieper and The Vistula rivers flow regime caused by the functioning of the dams were determined using IHA (Indicators of Hydrologic Alteration) and the RVA (The Range of Variability Approach) method. It was demonstrated that the operation of the hydroelectric power plant especially in the hydropeaking system is the cause of a large flow alteration in respect of the frequency and duration of low- and high-flow pulses and the rate and frequency of change in the flow. It was assessed how the change in flow conditions in connection with the deficit of sediments affected the transformation of the Vistula and Dnieper river channels downstream of the dams. Based on our results, the reaction of the fluvial system to changes in the flow regime caused by the operation of the Kaniv and Włocławek hydroelectric power plants consisted in: 1) changing the width and depth of channels; 2) changing the size of the forms separating channels; 3) fixation of the anastomosing fluvial system. More dynamic water flows due to the operation of hydroelectric power plants modify and dynamize the natural process of evolution of a fluvial system into an anastomosing system by causing the incision and narrowing of the main channels, because of which the side channels occupy a higher position above them. On the other hand, the equalization of the water flow in the channels causes a decrease in the water level and the disappearance of the flow in the side channels. As a result, the islands separated by these channels merge and inter-channel areas are formed.